PERAN KEPALA SEKOLAH DALAM MENINGKATKAN SUMBERDAYA PENDIDIKAN DI SD NEGERI 35/VI SELING KECAMATAN TABIR KABUPATEN MERANGIN - Aminah; Guswita, Reni (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Abstract This study aims to examine the role of the Principal in enhancing educational resources at SDN Seling, Tabir District, Merangin Regency. The Principal holds a central role in developing human resources, improving school facilities, and implementing morning routines that shape students' character. This research employs a qualitative descriptive method through interviews, observations, and document analysis. The findings indicate that the Principal at SDN Seling has successfully improved the quality of education through various programs and activities, such as teacher training, infrastructure enhancements, and religious and cleanliness activities. These results underscore the importance of effective leadership in achieving educational objectives, demonstrating that the Principal's initiatives play a significant role in advancing the educational standards at the school. This study highlights the critical impact of the Principal's efforts in fostering a supportive and enriching educational environment. Keywords : Role, Principal, Educational Resources